Tourism Destination Service Quality: An Analysis of Domestic Tourists Satisfaction In Kawasan Luar Pura Uluwatu - Supraba, Cening Ayu; Lilasari, Luh Nyoman Tri; Aridayanti, Dewa Ayu Nyoman (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
In 2022, Kawasan Luar Pura Uluwatu received several bad reviews regarding the quality of services provided. The aims of the study are 1) domestic tourists' satisfaction with service quality in the form of respondent's responses to tangibles, empathy, reliability, responsiveness and assurance in Kawasan Luar Pura Uluwatu, 2) The Importance of Performance Analysis on service quality in Kawasan Luar Pura Uluwatu. This study is a quantitative descriptive study with a sample of 100 domestic tourist respondents visiting Kawasan Luar Pura Uluwatu using a Purposive method. The Importance Performance Analysis (IPA) method was used in this study to determine the satisfaction level of domestic tourists. The results of this study indicate 1) tourists satisfied with the service quality in Kawasan Luar Pura Uluwatu with a total satisfaction level of 96,95%; 2) indicators of service quality included in the top priority category are the suitability of ticket prices with the products, facilities and service provided, officers respond well to tourist complaints, officers do not discriminate between tourists and ease in the service process that needs to be improved so that it gets special attention from the manager.